A study of the effectiveness of various methods of muscular relaxation : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Petersen, Daphne Elaine Leslie (Massey University, 1979)
This study was designed to compare the effectiveness of four different methods of skeletal muscle relaxation. Twenty four male, undergraduate student volunteers were recruited for this study, the age range was 18 to 31 years. The Experiment was conducted in two sections as time did not allow for the training of 24 Subjects concurrently. Section I was conducted over weeks one to eight inclusive and Section II was conducted over weeks nine to thirteen inclusive. All Subjects received two pre-test sessions which involved the measuring and recording of the level of tension which was present in three muscle groups, the occipitofrontralis, the right sternocleidomastoid and the right biceps. Muscle tension was measured using a Disa 3-channel Electromyogram, and recorded using a multichannel ultra-violet recorder. The Subjects were assigned to training groups (four Subjects per group) on the basis of visula inspection of the records, those with the highest levels of tension recorded were assigned at random between the groups, similarly those with medium Levels of tension and those with low levels of tension were assigned at random to the groups. The training methods in Section I were, Progressive Relaxation, Jacobson (1938) and Control Group C. The training methods in Section II were, Muscle Relaxation, Wolpe (1969), Metronome Conditioned Relaxation, Brady (1973) and Control Group F. When the training sessions were completed, each Subject received two post-test sessions, which were of the same format as the pre-test sessions. The data recorded was then scored and converted into an integrated E.M.G. Analysis of the results indicated that in most cases there was little, if any reliability between scores on pre-test I and pre-test II thus further quantitative analysis of the data was not appropriate. Graphic representation was made of group means for comparison between pre-test II and post-test I. It was expected that training in some of the methods would produce complete muscle relaxation, (or no tension as measured on the Electromyograph recordings.) The Subjects inability to achieve voluntary muscle relaxation may have been attributed to several factors in the design of the experiment. The Subjects were trained in a different room to the pre-test, post-test room. The recording from the muscle groups during pre-test, post-test sessions may well have interfered with the Subjects ability to relax. The stimuli presented to the Subjects during the testing sessions also appeared to contribute towards the Subjects inability to relax. The Experimenter's observations of the Subjects during the latter stages of training indicated that the Subjects in Jacobson's Garmany's and Wolpe's methods all appeared to achieve some level of relaxation which was not reflected in the results recorded.
Keywords: Muscles -- Relaxation